STUDI POTENSI PEMBANGKIT LISTRIK TENAGA GELOMBANG LAUT DENGAN METODA OSCILATING WATER COLUMN DI PERAIRAN KENDARI INDONESIA - Faulincia Faulincia (President University, 2019)
Referring to Law Number 30 of 2007 concerning Energy, the development of techniques the conversion of electrical energy by using alternative energy sources is interesting for followed for the past few years. This paper discusses calculation analysis power potential of ocean wave conversion using the Oscilating Water system Column (OWC) in the marine area of Indonesia. This system was chosen because it has many advantages compared to other systems and in accordance with the marine and coastal areas of Indonesia. From the calculation of power, the smallest power that can be produced is equal to 348.5838 Watts while the biggest power that can be produced is 623291.4 Watts The application of the oscillating water column system in Kendari waters with an efficiency of 11.971%.Keywords. oscillating water column (OWC), ocean wave energy, electrical energy, power potential,wavelength